Incidence of diabetes in HIV-infected patients treated with first-line integrase strand transfer inhibitors: a French multicentre retrospective study. (13th August 2020) - Ursenbach, Axel; Max, Vincent; Maurel, Marine; Bani-Sadr, Firouzé; Gagneux-Brunon, Amandine; Garraffo, Rodolphe; Ravaux, Isabelle; Robineau, Olivier; Makinson, Alain; Rey, David; ,
Abstract: Background: Integrase strand transfer inhibitors (INSTIs) are increasingly used in patients living with HIV due to their safety, effectiveness and high genetic barrier. However, an association with weight gain has recently been suggested and several cases of diabetes mellitus have been reported with raltegravir and dolutegravir. The long-time metabolic impact of these recent molecules remains unclear. Objectives: To assess if an INSTI as a third agent is statistically associated with new-onset diabetes mellitus compared with an NNRTI or a PI. Patients and methods: Patients undergoing first-line combined ART (cART) without diabetes at baseline were retrospectively included from the Dat'AIDS French cohort study (ClinicalTrials.gov NCT02898987). Incident diabetes mellitus was defined as a notification of new diabetes in the medical history, a glycated haemoglobin (HbA1c) level superior to 7.5% or the start of a diabetes therapy following the initiation of ART. Results: From 2009 to 2017, 19 462 patients were included, among which 265 cases of diabetes mellitus occurred. Multivariate and survival analyses did not highlight an increase in new-onset diabetes in patients undergoing cART with an INSTI as a third agent compared with an NNRTI or a PI. BMI >30 kg/m 2, age >37 years old (in survival analysis), black race or Hispanic ethnicity, arterial hypertension and AIDS were associated with a higher proportion of incident diabetes. Conclusions: INSTIs were not statistically associated with new-onset diabetes. However, clinicians should remain aware of this possible metabolic comorbidity, particularly in patients with a high BMI and older patients.